Bioethics for a socially responsable public health - Ortíz, María Iliana; Palavecino, Susana (Acta Bioethica, 2005)
Is it possible for economy sciences to offer a bioethics" contribution for Public Health? Our aim was to establish a dialogue with economic trends developed during the last decades and to see how and up to what extent they can contribute to Public Health within the Latinamerican context. For this purpose we individualized some social responsibility indicators undertaken by enterprises that tried to apply those tendencies. We studied the effects that could be caused when applying them to certain bioethical issues presented by Public HealthÕs management. We found a favourable "humus" to approach the dilemmas that were set up within the cultural patterns that these tendencies establish. We also distinguished new clues that could help revert undesirable attitudes of the health management which are present at the State, society and private enterprises.